Tax coordination, tax competition, and revenue mobilization in the west african economic and monetary union - Mario Mansour; Grégoire Rota-Graziosi (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
We review the current state of the West African Economic and Monetary Union's (WAEMU) tax coordination framework, against the main objectives of the WAEMU Treaty of 1994: reduce distortions to intra-community trade, and mobilize domestic tax revenue. The process of tax coordination in WAEMU is one of the most advanced in the world—de jure at least—, but remains in many areas ineffective de facto. The framework has, to some extent, ucceeded in converging tax systems, particularly statutory tax rates, and may have contributed to improving revenue mobilization. Important lessons can be drawn from the WAEMU experience, especially in terms of whether coordination should take the form of harmonization through a topdown approach, or a softer approach of sharing best practice and limiting certain types of harmful tax competition.
Keywords: O1; H2; H7; 330